Optimal distribution of temperature driving forces in low‐temperature heat transfer. Issue 8 (20th April 2015) - Austbø, Bjørn; Gundersen, Truls
<x xml:space="preserve">Abstract</x> A fairly extensive review of research on optimal distribution of driving forces in heat‐transfer processes is provided. Four different guidelines for specifying the temperature profiles in heat exchangers have been compared. Not surprisingly, the irreversibilities due to heat transfer in a heat exchanger of given size were found to be minimized when the temperature difference is proportional to the absolute temperature. Comparing a design with an optimal temperature profile and a design with a uniform temperature difference throughout the heat exchanger, sensitivity analyses illustrated that savings in irreversibilities increase with decreasing temperature level and increasing temperature span for the cooling load. Heat exchanger size was found to be of negligible importance. The results indicated that optimal utilization of heat exchanger area is of little importance for processes operating above ambient temperature, while significant savings can be obtained by optimal distribution of temperature driving forces in processes below ambient temperature. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2447–2455, 2015